2021
DOI: 10.3389/fimmu.2021.708848
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus-2 Infection and Autoimmunity 1 Year Later: The Era of Vaccines

Abstract: Impressive efforts have been made by researchers worldwide in the development of target vaccines against the novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) and in improving the management of immunomodulating agents. Currently, different vaccine formulations, such as viral vector, mRNA, and protein-based, almost all directed toward the spike protein that includes the domain for receptor binding, have been approved. Although data are not conclusive, patients affected by autoimmune rheumatic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 166 publications
(196 reference statements)
1
5
0
Order By: Relevance
“…Also, only 5 patients reported mild COVID‐19 symptom and none of the patients had been hospitalized because of COVID‐19. Hence, in line with previous reports on patients with AIH 15 and other autoimmune diseases, 16,17 patients with autoimmune liver diseases were not at high risk of a severe disease course.…”
Section: Discussionsupporting
confidence: 90%
“…Also, only 5 patients reported mild COVID‐19 symptom and none of the patients had been hospitalized because of COVID‐19. Hence, in line with previous reports on patients with AIH 15 and other autoimmune diseases, 16,17 patients with autoimmune liver diseases were not at high risk of a severe disease course.…”
Section: Discussionsupporting
confidence: 90%
“…In the effort of increasing the chances of complete protection, additional strategies may be explored such as a longer suspension of immunosuppressive agents during the vaccine administration, as well as the switch to drugs that have mechanisms of action with a reduced impact on vaccine immunogenicity ( 13 ). The use of a heterologous vaccination may help in enhancing the immune response, as recently reported by a systematic review in the general population, although the immunogenicity was higher in the population vaccinated with ChAdOx1-S followed by BNT162b2 rather than vice versa ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these studies show that the humoral response to BNT162b2 vaccine is immunogenic in the majority of RA patients, although the response is delayed and decreased compared to controls ( 10 ). In particular, we showed that RA patients have a lower quantitative immune response (both antibody- and T cell-specific responses) to BNT162b2 vaccine compared to a control group of health care workers (HCWs), even if the vaccine is qualitatively immunogenic for most RA patients ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Th17 hyperactivation and disturbances in their subpopulation composition, changes in the ratio of “regulatory” and “pro-inflammatory” Tfh cells as well as a decrease in the control of antibody-producing B cells are very similar to changes, characteristic of a wide range of autoimmune pathologies [ 122 , 123 ], the incidence of which increases sharply after COVID-19 [ 124 ]. Long-term disturbances in the processes of maturation and differentiation of NK-cells and cytotoxic T-lymphocytes, the presence of inhibitory receptors or markers of “cellular aging” on their surface which is accompanied, first of all, by low efficiency of destruction of target cells may reduce the effectiveness of antitumor and antiviral immunity [ 125 , 126 , 127 ].…”
Section: Post-covid-19 Syndrome or Long-covid-19: Heart Disease In Ch...mentioning
confidence: 99%